MACC1 Is Associated With Epithelial–Mesenchymal Transition and Can Predict Poor Prognosis in Nasopharyngeal Carcinoma - Cheng, Hao; Zhou, Linxiang; Long, Yalan; Xiang, Juanjuan; Chen, Longhua (Frontiers in Oncology, 2021)
Background Given the reported correlation between the oncogene metastasis-associated in colon cancer 1 (MACC1) and nasopharyngeal carcinoma (NPC), as well as between MACC1 and epithelial–mesenchymal transition (EMT), we speculated that EMT is a likely causative link between MACC1 expression and poor NPC prognosis. Thus, we aim to clarify the relationship between MACC1 and EMT in NPC prognosis. Material and Methods We performed immunohistochemical examination of tissue sections from 128 NPC patients that were divided into six groups corresponding to high and low protein expression of MACC1 and two EMT-related proteins, vimentin and E-cadherin, and Kaplan–Meier (KM) survival analyses were performed. Results KM survival analysis showed that upregulation of MACC1 and vimentin and downregulation of E-cadherin were significantly associated with reduced survival in NPC. Short hairpin RNA (shRNA) interference and immunoblotting in the NPC cell line HNE-1 led to increased E-cadherin but decreased vimentin levels. MACC1 overexpression was significantly correlated with poor 5-year overall survival, metastasis-free survival, and disease-free survival (P<0.05) but not with poor relapse-free survival (P>0.05). Univariate analyses revealed that MACC1, E-cadherin, and vimentin levels along with T and N tumor classifications and cancer staging are significant prognostic factors of NPC (P<0.05). Conclusion Our findings showed the association between MACC1 and EMT in NPC malignancy and support the role of MACC1 as a prognostic biomarker and molecular target for NPC treatment.